The ecological importance of mixed-severity fires : nature's Phoenix - DellaSala, Dominick A., 1956-; Hanson, Chad T. (Elsevier, 2015)
The Ecological Importance of High-Severity Fires, presents information on the current paradigm shift in the way people think about wildfire and ecosystems. While much of the current forest management in fire-adapted ecosystems, especially forests, is focused on fire prevention and suppression, little has been reported on the ecological role of fire, and nothing has been presented on the importance of high-severity fire with regards to the maintenance of native biodiversity and fire-dependent ecosystems and species. This text fills that void, providing a comprehensive reference for documenting and synthesizing fire's ecological role.